The Relationship Between Self Efficacy and Self Regulated Learning in Students in Bukittinggi - Utami, Eliza Sutri (Westscience Press, 2023)
The relationship between self-efficacy and self-regulated learning in students in Bukittinggi. This study aims to see the relationship between self-efficacy and self-regulated learning in students in Bukittinggi. The population in this study was students at 15 universities in Bukittinggi with stratified proportional random sampling technique. The data collection tool used a self-efficacy scale and a self-regulated learning scale. Data analysis technique using product moment correlation test from Karl Pearson using SPSS 16.0 for windows. The results proved that there was a positive relationship, tevident from the results of the hypothesis test obtained a correlation coefficient rxy of 0.841 and p = 0.000 (p < 0.05).